2017
DOI: 10.1159/000481090
|View full text |Cite
|
Sign up to set email alerts
|

The RAPID Neuropsychological Test Battery for Subjects Aged 50–89: From Norms to Cognitive Profile

Abstract: Background/Aims: It is well established that healthy adults obtain low performances when simultaneously interpreting the results of multiple tests. The aim of this study was to estimate the proportion of French-speaking healthy older adults with low scores for the RAPID (Réseau d’Aide au diagnostic et à la PrIse en charge des Détériorations cognitives et de maladies neurologiques chroniques en Franche-Comté et au niveau national) battery test and consider different combinations of test scores within a specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The 5th percentile cut-off values for the 13 primary measures of the RAPID test battery were calculated in a previous study (Sylvestre et al, 2017 ) from the normative sample of older adults (Ferreira et al, 2010 ) based on three age categories (ranges 60–69, 70–79, and 80–89 years) and three educational levels: high level (i.e., >11 years of education), middle level (i.e., 8–11 years of education), or the lowest educational level (i.e., <8 years of education).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The 5th percentile cut-off values for the 13 primary measures of the RAPID test battery were calculated in a previous study (Sylvestre et al, 2017 ) from the normative sample of older adults (Ferreira et al, 2010 ) based on three age categories (ranges 60–69, 70–79, and 80–89 years) and three educational levels: high level (i.e., >11 years of education), middle level (i.e., 8–11 years of education), or the lowest educational level (i.e., <8 years of education).…”
Section: Discussionmentioning
confidence: 99%
“…They are consistent with previously reported studies on other neuropsychological test batteries (Heaton, 1991 ; Palmer et al, 1998 ; Brooks et al, 2009a , 2011 ; Karr et al, 2017 ) and confirmed that low scores are common in healthy older people when multiple test scores are simultaneously analyzed across a battery. This implies that isolated low scores obtained by an individual across multiple tests are not necessarily pathological or indicative of truly impaired functioning (Schretlen et al, 2008 ; Binder et al, 2009 ; Sylvestre et al, 2017 ). Thus, our data showed that from 9.4 to 17.6% of healthy older people obtained at least one low score on either measure in each cognitive domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations